2008
DOI: 10.1021/jp8034659
|View full text |Cite
|
Sign up to set email alerts
|

Divisive Effect of Alcohol−Water Mixed Solvents on Growth Morphology of Calcium Carbonate Crystals

Abstract: Controlling the process of crystal growth is of importance to the biomineralization and materials science. In this work, some novel morphology of calcium carbonate (CaCO 3 ) was precipitated in an ethanol-water binary solvent (EWBS) with a CaCl 2 /Na 2 CO 3 reaction system. For the solutions of CaCl 2 /Na 2 CO 3 in EWBS, the alcoholization and hydration of Ca 2+ and CO 3 2were discussed from the radial distribution functions by molecular dynamics simulations, and the number density profiles of water molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 30 publications
2
43
0
1
Order By: Relevance
“…[26][27][28] In addition, Anhydrous calcium chloride and ammonium carbonate were dissolved in absolute ethanol, and then the solutions were added to absolute ethanol, or other alcohols, using syringe pumps under continuous magnetic stirring until the desired concentration was reached (see the Experimental section in the ESI †).…”
Section: -26mentioning
confidence: 99%
“…[26][27][28] In addition, Anhydrous calcium chloride and ammonium carbonate were dissolved in absolute ethanol, and then the solutions were added to absolute ethanol, or other alcohols, using syringe pumps under continuous magnetic stirring until the desired concentration was reached (see the Experimental section in the ESI †).…”
Section: -26mentioning
confidence: 99%
“…For example, Zhou et al 42 precipitated vaterite with a wide range of morphologies, including cauliflower spheres, by varying pH, Ca/CO 3 ratios and temperature, without using alcohol. Furthermore, Manoli and Dalas 16 reported the development of two different types of cauliflower spheres by varying the type of alcohol (ethanol, isopropanol, and diethylene glycol), and Zhang et al 24 reported that cauliflower vaterite formed in the presence of ethanol but accompanied by aragonite. They concluded that by varying the Ca/CO 3 ratio, they could define the relative proportions of aragonite and vaterite.…”
Section: Scheme 1 Simplified Morphological Evolution With Time For Tmentioning
confidence: 99%
“…Zhang et al 24 investigated the alcoholization and hydration of Ca 2+ and CO 3 2− , using molecular dynamics simulations. They reported that CO 3 2− ions in ethanol−water mixtures are mainly solvated by water and hardly dissolve in ethanol, whereas Ca 2+ ions are solvated both by water and by ethanol.…”
Section: Scheme 1 Simplified Morphological Evolution With Time For Tmentioning
confidence: 99%
“…Vaterite precipitates were prepared by a chemical reaction in water-ethanol binary solvent by mixing WEBS solutions of Na 2 CO 3 and CaCl 2 , as reported in our previous paper [13]. under these conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Morphology and phase evolution of vaterite crystal in WEBS was under research. Using theoretically calculated data [13] of calcium carbonate, we tried to interpret the experimental results.…”
Section: Introductionmentioning
confidence: 99%